Application of ablation techniques in the treatment of lung cancer - a review of recent reports - Klas, Jakub Michał; Pytka, Michalina; Piwowar, Klaudia; Kulszo, Katarzyna (Journal of Education, Health and Sport, 2022)
Background: Lung cancer is the second most common and fatal cancer worldwide. The first-line treatment for early-stage primary lung cancer is surgical resection, but surgery is contraindicated in 60% of cases. Alternatives then include local treatments such as radiofrequency ablation (RFA), microwave ablation (MWA) and cryoablation. With the current scientific knowledge of these treatments, the fundamental question of their therapeutic efficacy must be answered. Aim and methods: To present recent scientific findings on the efficacy of the three main methods of thermoablation for lung cancer. A systematic review of scientific papers on the indicated topics from the last 5 years was performed. Several dozen publications were selected for the purpose of this study. Results: As shown in the studies, the therapeutic effect of MWA controls tumour progression with few side effects and high safety, especially in patients with tumours <3.5 cm in diameter. Cryotherapy, on the other hand, not only improves quality of life, but can also prolong patients' survival. The relatively low risk of this procedure goes hand in hand with its minimal invasiveness, leading to a low complication rate. RFA, on the other hand, shows no greater treatment efficacy than surgical resection, stereotactic radiotherapy. Conclusions: MWA and cryoablation techniques are interesting alternatives to surgical resection for non-small cell lung cancer, improving the quality of life of patients regardless of the stage of their disease. The question of increasing the availability of this type of treatment in the health care system therefore remains crucial.